Do consumers in Pakistan understand the concept of generic medicines? A quantitative insight - Siddiqui, Mohammad Jamshed Ahmad; Jamshed, Shazia Qasim; Ibrahim, Mohamed Izham; Hassali, Mohamed Azmi; Babar, Zaheer-ud-din; Alkalami, Ramdan (Elsevier, 2012)
Objectives: Developing countries are struggling with the high cost of treatment and generic medicines could be instrumental in curtailing the cost of treatment and reduce healthcare expenditures. Pakistan is not an exception to this issue. This study is a mere attempt to explore the knowledge and perception of Pakistani consumers towards generic medicines. Methods: Three hundred questionnaires were interview administered to a quota sample of Pakistani consumers. This type of sampling could assist in assuring the inclusion of those respondents that could be likely underrepresented in convenience sampling. Gender and income group were considered as quota control variables. The criterion was chosen because for gender there is equal chance of selection of both males and females. Moreover, income group was considered another quota control variable because for generic medicines cost is obviously the most important reason for selection of generic medicines. Results: The mean age of the respondents was 46.5 11.38. Out of 300 respondents 167 (55.7%) were found to be male while the remaining 133 (44.3%) were found to be female. A very few respondents from high income group had medical insurance coverage (n¼30; 10.0%). A very large majority of consumers never heard the term generic medicines (n¼207; 69%). Slightly less than half of the respondents agreed (n¼135; 44.0%) that low cost medicines are as effective as brand medicines. A very large majority agreed (n¼254; 84.7%) that their doctor prescribes the best medicine for them. More than half of the respondents expressed their comfort to switch from one brand to another because of low cost potential. A very large majority of the respondents showed their outlook (n¼258; 86.0%) that doctors should talk about the cost before writing a prescription. Conclusions: The study demonstrated gaps in the knowledge of generic medicines but somewhat, good perception was noted among consumers.